2019
DOI: 10.1177/0022042619847220
|View full text |Cite
|
Sign up to set email alerts
|

Risk Seeking Moderates the Association Between Emotion Dysregulation and Cannabis-Related Consequences

Abstract: Sensation seeking and emotion dysregulation have been identified as contributing factors for consequences associated with cannabis use, although findings have been mixed. The study seeks to clarify relations between sensation seeking, emotion dysregulation, and cannabis-related consequences. Cannabis users (N = 2,128) were assessed for facets of sensation seeking, emotion dysregulation, and cannabis-related consequences. Results revealed a positive association between risk seeking and cannabis-related conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Past research indicates that cognitive processes (such as cannabis refusal self-efficacy, cognitive reappraisal of emotions, and premeditation) are strategies effectually moderating predictive associations between high-risk traits, coping use motives, and negative use consequences ( Bonn-Miller at al., 2008 ; Brook et al, 2016 . ; Cerdá et al, 2016 ; Dvorak & Day, 2014 ; Kentopp at al., 2019 ; Pearson at al., 2018 ; Prosek et al, 2018 ; VanderVeen, 2016 ). Given this, we sought to further understand the potential effect of rumination (as a form of cognitive processing), potentially linking the associations between distal predictors, cannabis coping motives, and negative use consequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past research indicates that cognitive processes (such as cannabis refusal self-efficacy, cognitive reappraisal of emotions, and premeditation) are strategies effectually moderating predictive associations between high-risk traits, coping use motives, and negative use consequences ( Bonn-Miller at al., 2008 ; Brook et al, 2016 . ; Cerdá et al, 2016 ; Dvorak & Day, 2014 ; Kentopp at al., 2019 ; Pearson at al., 2018 ; Prosek et al, 2018 ; VanderVeen, 2016 ). Given this, we sought to further understand the potential effect of rumination (as a form of cognitive processing), potentially linking the associations between distal predictors, cannabis coping motives, and negative use consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established certain personality traits as distal antecedents of cannabis use and negative consequences of cannabis use (e.g., Dvorak & Day, 2014 ; Kentopp et al, 2019 ; Pearson et al, 2018 ). Such traits include sensation seeking, impulsivity, and emotion dysregulation.…”
Section: Personality Traits As Predictors Of Use and Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Several cross-sectional studies described an association between higher scores on self-reported impulsivity measures and the experiences of CRNCs. 44,57,[69][70][71] Sensation seekingthe trait of seeking novel and intense experiences-was also significantly associated with CRNCs 45,70,72 with one exception, a significant, negative association to CRNCs among persons with relatively low use of protective behavioral strategies (ie, acting as a mediator for the risk and protective factors of cannabis consequences). 73 There were no longitudinal studies investigating this relationship identified in our search.…”
Section: Intrapersonal Influencesmentioning
confidence: 98%